On a Software Tool for Implementation of Systolic Algorithms in the Cluster Environment - Davtyan, Edmon M. (Mathematical Problems of Computer Science, 2024)
In this paper a software tool SAS (Systolic Algorithm Simulator) is designed to model the work of a one-dimensional systolic array of n cells on a homogenous computational cluster of m « n processors. As a result of the program execution, a cluster-based programming module is obtained, where computational resources of the system are used in an effective way.